PENGARUH IMPLEMENTASI KEBIJAKAN REFORMASI BIROKRASI TERHADAP PENERIMAAN PENDAPATAN ASLI DAERAH KABUPATEN MINAHASA TENGGARA - Tumiwa, Valen; Posumah, Jhonny Hanny; Kiyai, Burhanuddin (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : Governance of area can walk because of existence of support various resource factorcapable to move organizational wheel of governance in order to attainment of target management of areaautonomy, including in it is Earnings Of Genuiness Area. Problem of which in questioning in thisresearch is how a far influence of Implementation Policy Of Reform Bureaucracy To Revenue OfGenuiness Area Sub-Province of Minahasa South-East".Method which used in this research isquantitative method. this Research Subyek is public servant of civil in On Duty Earnings Of Area Sub-Province of Minahasa South-East. Sampel Research taken by counted 39 people, consist of 23 people ofPNS and the rest counted 16 people officer honorer.data collecting by using kuesioner Result of dataanalysis After calculated by using correlation analysis of product assisted moment with analysis of tools ofprogram of Exel, hence obtained by correlation coefficient of Implementation Policy Of ReformBureaucracy ( X) to Earnings Of Genuiness Area ( Y) is real and positive and correlation coefficient andalso determinasi reside in at high category. Relate at pickings analyse data which have been elaborated byprevious shares, hence it is can be pulled by some final conclusion as follows.1. Implementation policy of bureaucracy reform represent one of the determinant revenue of areagenuiness.2. Result of statistical analysis indicate that between implementation policy of bureaucracy reform withrevenue of area genuiness have relation of kontributif and have positive linear pattern . Relation both ofvariable very signifikan at level test 1%, whereas degree of determinant energy equal to 87,8%. Mountingand or down it revenue of Genuiness Area Sub-Province of Minahasa South-East equal to 87,8 %determined by Reform Bureaucracy factor.Keyword : Implementation Policy, Revenue Of Genuiness Area